Bahasa Inggris Perancangan Interior Bertema Jawa Timur pada Restoran Hallo Surabaya Kertajaya untuk Pelestarian Budaya - Kristina, Ardine Fincelia; Santosa, Adi; Poillot, Jean Francois (Serat Rupa: Journal of Design, 2026)
Interior design in restaurants not only serves as a setting for food presentation but also functions as a medium for representing cultural identity. In the context of ethnic restaurants, the spatial atmosphere created through interior elements plays a crucial role in shaping an authentic dining experience. This study aims to analyze the application of East Javanese cultural elements in the interior design of Hallo Surabaya Kertajaya Restaurant as an effort to preserve Surabaya’s local culture. The background of this research arises from the growing tendency of urban communities to appreciate local values, both in culinary practices and spatial ambiance. A qualitative descriptive approach with a case study method was employed in this study. Data were collected through field observations, interviews with restaurant owners and users, and literature studies related to interior design and East Javanese culture. The design process was analyzed using the design thinking framework as a tool for analysis and design development. The results indicate that the integration of Arek Surabaya cultural elements—such as distinctive batik motifs, the use of local materials (wood, bamboo, and rattan), symbolic ornaments, and warm, adaptive spatial characteristics—strengthens the restaurant’s identity and enhances the overall quality of the spatial experience. These findings confirm that interior design based on local cultural values not only contributes to cultural preservation but also improves spatial atmosphere and user comfort.